Comparative analysis of the definitions of logistics centres - Meidute, Ieva (Transport, 2005)
A logistics centre is a center for all the companies which participate in activities related to transport and logistics in the broadest meaning. LCs provide collective equipment needed to develop these activities and have common services for the companies installed there. Together with the values of location and centrality a logistics centre provides quality service and effective selection of the most efficient means of transportation due to its truly multi‐modal transport possibilities.First Published Online: 27 Oct 2010